The Return of Religion and the Problem of Radical Evil: A Case Study of Russia’s War in Ukraine - Bacevičiūtė, Danutė (Religija ir kultūra, 2019)
The article analyses the case of Russia’s war in Ukraine by focusing on the ambivalent relationship between radical evil and the “return of the religious”. First, the revival of politicised religious fundamentalism in contemporary Russia is examined by discussing the relationship between the state and the church and its concretisation in the field of foreign policy – the “Russian World” teaching. The article shows how the Russian Orthodox Church legitimises a project that pursues geopolitical goals and justifies the started war as a metaphysical fight against evil. Attention is drawn to the fact that in this case we are dealing with a kind of “secular religion” or “inverted secularism”, when ecclesial forms are used to revive the Soviet imperialism, and faith is replaced by beliefs. Next, when considering the analysed case in the context of the “return of the religious” reflected by Jacques Derrida and Gianni Vattimo, the emphasis is not only on the principle of violence (which is born from the fusion of political and religious discourses), but also on the positive possibilities of this return, which aforementioned thinkers elaborated by formulating the concepts of elementary faith and ethics of charity. At the same time, the article shows that these concepts lack an existential focus that would allow the problem of radical evil to be grasped at the level of individual existence. Therefore, to highlight the existential aspect of radical evil, the concepts of the perverse will, “grey zone” and impossible hope are used.
Keywords: Russia’s war in Ukraine; “Russian World”; return of the religious; politicised religious fundamentalism; secularisation; radical evil; perverse will; “grey zone”; impossible hope